Cadmium Levels in Tissue and Plasma as a Risk Factor for Prostate Carcinoma: a Meta-Analysis - Zhang, Liang; Yi Zhu; Rui Hao; Mengmeng Shao; Yunbo Luo (Biological trace element research, 2016)
Cadmium is a heavy metal that has been suggested to be a carcinogen by evidence. A number of published studies have investigated the association between cadmium levels and prostate cancer, but the results were inconsistent. Thus, we conducted a meta-analysis to get a precise estimate of this subject. After a careful searching and screening, a total of 11 publications containing 14 separated studies were included. Based on a random-effect model, the pooled data showed that cadmium levels of prostate tissues (standard mean difference (SMD)â=â3.17, 95Â % confidence interval (CI)â=â0.60â5.74, Pâ